2005
DOI: 10.1007/s11262-005-1791-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Canine Parvovirus VP2 Gene in Taiwan

Abstract: Canine parvovirus (CPV) is a non-enveloped virus with a single-stranded DNA genome and causes infectious enteritis in dog. In this study, 36 isolates of CPV infection were obtained in Taichung, Taiwan from 2003 to 2004. Using primers that can distinguish subtypes of CPV, we amplified part of viral VP2 gene by polymerase chain reaction (PCR) and the PCR product was sequenced; results demonstrated that two isolates could be classified as type 2a of CPV and the others were type 2b. The complete coding region of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 10 publications
6
38
0
Order By: Relevance
“…A summary of our own experience of CPV detection during the last 8 years is presented in Table 6, which confirms that the sensitivity of VI (75.6%) is indeed lower than that of PCR (93.9%) although specificity is higher with VI (98.8%) than with PCR (94.1%). Therefore, as already described by ourselves and others [12,36], molecular methods such as PCR may be superior to others for routine detection of CPV and are very useful when known types of CPV are investigated in a large number of field samples [6,8,9,11,15,21,22,28,33,48,59]. In the present study, our routine PCR did reveal that the field CPV-2a or 2b viruses were decisively associated with all clinical cases ( Table 1).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A summary of our own experience of CPV detection during the last 8 years is presented in Table 6, which confirms that the sensitivity of VI (75.6%) is indeed lower than that of PCR (93.9%) although specificity is higher with VI (98.8%) than with PCR (94.1%). Therefore, as already described by ourselves and others [12,36], molecular methods such as PCR may be superior to others for routine detection of CPV and are very useful when known types of CPV are investigated in a large number of field samples [6,8,9,11,15,21,22,28,33,48,59]. In the present study, our routine PCR did reveal that the field CPV-2a or 2b viruses were decisively associated with all clinical cases ( Table 1).…”
Section: Discussionsupporting
confidence: 73%
“…This is a non-synonymous substitution that does not result in an antigenic change and thus new CPV-2a and 2b are genetic but not antigenic variants of the prototype CPV-2a and 2b. Today, the new CPV-2a and 2b have become the predominant CPV throughout the world, although the relative proportion of antigenic types varies from country to country [8,9,13,15,21,28,33,38,48,56,59]. Our recent study indicates that the new CPV-2b has been predominant since 1997 over the field of Japan [39].…”
mentioning
confidence: 87%
“…2). The results were in agreement with those reported by Hirasawa et al [7] in Japan, Steniel et al [19] in South Africa, Pereira et al [14] in Brazil, Wang et al [24] in Taiwan and Hong et al [8] in US. In a recent report Sanjukta et al [17] also reported CPV-2b as the prevalent strain in certain North Indian states.…”
supporting
confidence: 93%
“…As it was expected and reported previously (Decaro et al 2009) all the CPV-2c VP2 sequences formed a monophyletic cluster (cluster 7). Despite the strong phylogenetic association with CPV-2a ancestor, the Lithuanian CPV VP2 sequences show more or less geographically defined evolution pattern (especially five CPV samples in the first cluster), as were identified in other regions and studies (Battilani et al 2002, Wang et al 2005, Kang et al 2008. Phylogenetic analysis showed some evidence for geographical clustering at an international level, suggesting that currently there are limited opportunities for global transmission, as has previously been suggested by others (Hoelzer et al 2008).…”
Section: Discussionmentioning
confidence: 49%